An Experimental Program Using Carbon Rod Geometry and Particle Image Velocimetry (PIV) to Investigate the Ground Response Affected by Adjacent Tunneling - Baek, Munkyeong; Chankee, Jung; Chang, Ilhan (Geotechnical Special Publication, 2023)
The behavior of soil relaxation in the ground produced by numerous reasons such as cavities, sinkholes, and tunnel excavation in the ground was confirmed in an experiment. To imitate the two-dimensional model ground in the experiment, the geometry was made out of carbon rods. It comes in three different diameters and is distributed at random. The ground's relaxation was indicated by the structure at the bottom of the experiment, which was used to induce deformation. During the experiment, taken pictures, particle image velocimetry (PIV) analysis was used to examine the behavior of soil particles during ground relaxation. The ground strain is used to express the deformation, and the critical range can be established. Visual confirmation of the results is possible by following the movement and deformation of carbon rod particles. Surface sinking and the behavior of the surrounding ground were confirmed by vectors and contours by simulating the onset of relaxation at various depths of the ground. It is feasible to comprehend the behavior and relaxation range of the surrounding ground using the methods described above when the ground relaxes according to depth. It is feasible to comprehend the issues created by ground relaxation in the subsurface space by doing so. Furthermore, if an underground structure exists, it is possible to identify and predict the movement and deformation of the structure as a result of ground relaxation, as well as to design a cost-effective and stable tunnel by predicting the behavior of the surrounding structures.
Keywords: Carbon rod; Experimental program; Geometry images; Ground response; Image velocimetry; Movement and deformations; Particle images; Rod geometry; Tunnel excavation; Two dimensional model